2018
DOI: 10.1111/epi.14510
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy surgery near or in eloquent cortex in children—Practice patterns and recommendations for minimizing and reporting deficits

Abstract: The wide variation in strategies may contribute to undesirable outcomes characterized by poor seizure control with added deficits and underscores the need to establish best practices in pediatric epilepsy surgery. The survey data were used to formulate a set of recommendations to help minimize deficits and to report them consistently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…[10][11][12][14][15] Furthermore, large-scale studies in adults and more diverse populations (pediatric patients and patients with epilepsy) are not feasible because of continued decline in the use of invasive techniques. Many epilepsy and neurosurgery centers now rely on functional magnetic resonance imaging (MRI) for presurgical language mapping [16][17][18] because it has been validated against invasive methods. [19][20][21] This widespread use of functional MRI allows for a broader verification of TMS-determined language maps in a diverse patient population.…”
mentioning
confidence: 99%
“…[10][11][12][14][15] Furthermore, large-scale studies in adults and more diverse populations (pediatric patients and patients with epilepsy) are not feasible because of continued decline in the use of invasive techniques. Many epilepsy and neurosurgery centers now rely on functional magnetic resonance imaging (MRI) for presurgical language mapping [16][17][18] because it has been validated against invasive methods. [19][20][21] This widespread use of functional MRI allows for a broader verification of TMS-determined language maps in a diverse patient population.…”
mentioning
confidence: 99%
“…• Patients with diffuse or bilateral ictal scalp EEG had a higher probability of disclosing an intralesional or perilesional activation during WG task than patients with focal ipsilateral ictal scalp EEG (OR = 12.83, p = 0.031, LR χ 2 (1) = 6.51 p = 0.011, Pseudo R 2 = 0.19 and OR = 6.27, p = 0.05, LR χ 2 (1) = 4.47 p = 0.034, Pseudo R 2 = 0.09, respectively).…”
Section: Plos Onementioning
confidence: 98%
“…Regression models showed that LI during comprehension task became more atypical when age at seizure onset increased (regr. coeff = -0.051; p = 0.036, LR χ 2 (1) = 4.93 p = 0.026, Adj R 2 = 0.15) and if patients were left-handed (regr. coeff = -0.6; p = 0.020, LR χ 2 (1) = 6.02 p = 0.014, Adj R 2 = 0.19).…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations